2018
DOI: 10.3892/etm.2018.6225
|View full text |Cite|
|
Sign up to set email alerts
|

MIST1 regulates SNAI1 and acts through the PTEN/AKT signaling axis to promote anoikis resistance in human melanoma cells

Abstract: Cutaneous malignant melanoma (CMM) is one of the most dangerous types of skin cancer. The prognosis of CMM patients with ulcers, regional lymph node metastasis or organ metastasis is poor. In this process, resistance to anoikis is a critical step in tumor cell metastasis. Tumor cells survive in the vascular and lymphatic system through the escape of anoikis to finally form clones in the distal tissue. The present study revealed that muscle intestine and stomach expression 1 (MIST1), a secreting cell-restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…MIST1 reportedly hijacks the PTEN-AKT signaling pathway to promote anoikic resistance in skin cancer 15 . Therefore, we investigated whether MIST1 contributes to HCC development by regulating the PTEN-AKT pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MIST1 reportedly hijacks the PTEN-AKT signaling pathway to promote anoikic resistance in skin cancer 15 . Therefore, we investigated whether MIST1 contributes to HCC development by regulating the PTEN-AKT pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Muscle intestine stomach expression 1 (MIST1), also known as BHLHA15, belongs to the basic helix-loop-helix (bHLH) superfamily, which plays a dual role in cancer development. MIST1 is regarded as a tumor promoter in multiple cancers, including cervical cancer 12 , colon cancer 13 , acinic cell carcinoma 14 , and cutaneous malignant melanoma 15 . However, previous studies have shown that upregulation of MIST1 reverses epithelial-mesenchymal transition (EMT) and attenuates the tumorigenicity of pancreatic cancer and gastric cancer 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have reported the pivotal role of anoikis resistance in lymphatic metastasis of cancer (10,11), even in lymphatic metastasis of thyroid cancer (18)(19)(20). Furthermore, anoikis resistance was reported to be significantly correlated with positive lymph node metastasis in various cancers (12)(13)(14)(15)(16)(17). In this scenario, multiple signaling pathways have been demonstrate to promote anoikis resistance, including TGF-b, PI3K/AKT, and Hippo signaling, where the role of Hippo signaling in inducing anoikis resistance gains more attention (9,50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the critical role of anoikis resistance in lymphatic metastasis of cancer seizes great attention ( 10 , 11 ). In several cancer scenario, anoikis resistance correlated significantly with positive lymph node metastasis status, including esophageal carcinoma ( 12 , 13 ), melanoma ( 14 ), tongue cancer ( 15 ), breast cancer ( 16 ), and colorectal cancer ( 17 ). Importantly, development of anoikis resistance has been reported to significantly contribute to lymphatic metastasis of thyroid cancer ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Mist1 in human gastric development and maturation has been described in recent years, and Mist1 has been suggested to regulate the maturation of exocrine granules via the RAB26/RAB3D complex and act a chief cell marker of gastric mucosa regeneration [17,20,27]. Recently, an increasing number of studies have addressed the role of Mist1 in the carcinogenesis and development of pancreatic cancer, melanoma and salivary gland acinic cell carcinoma [28][29][30]. Here, in our study, we found that Mist1 was downregulated in gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%